Licorice (Glycyrrhiza glabra) and its derivative (Glycyrrhizic and glycyrrhetinic acid) in finfish aquaculture: A review - Kenneth Prudence Abasubong; Jean-Jacques Y. Adjoumani; Guang-Zhen Jiang; Wen-bin Liu; Xiang-Fei Li; Xiu-Fei Cao; Hesham Eed. Desouky (Aquaculture Reports)
Aquaculture production is gradually increasing to meet the global demand for animal proteins. Aquaculture employs a range of feed additives to boost fish growth, immune system function, disease prevention, and antioxidant status. In intensive farming systems, fish reared at high densities may experience stress and become more susceptible to many diseases that could result in financial losses. Therefore, effective feeding techniques that include health-promoting substances, such as triterpenoids, saponins, and flavonoids, which can boost fish defense systems and improve growth, are priorities for the development of sustainable aquaculture. The major metabolites of licorice roots (Glycyrrhiza species), such as glycyrrhizic acid and glycyrrhetinic acid, have been shown to possess several biological properties, including liver protection, immunological modulation, and antimicrobial, antioxidant, and anti-inflammatory effects in aquatic animal species. Glycyrrhizic and glycyrrhetinic acid, when added in moderation to aquafeeds, may enhance fish growth, feed utilization, immune system performance, and disease resistance. As a natural compound, licorice is considered harmless to fish and the environment. With an interest in licorice and its derivative as an aquafeed supplement, this review sought to provide an overview of the applications, methods of production, and effects that have been documented on fish growth, immunological response, and disease resistance when licorice roots and their derivatives were added as feed additives.